Crude extraction and purification of IgY against Aeromonas hydrophila and its antibacterial activity in vitro - LI Xiao-liang; YIN Zhao-zheng; QIAN Ya; ZHU Zhi-gang; FANG Wei-huan (浙江大学学报. 农业与生命科学版)
Using water-dilution to extract crude IgY from egg yolk of hens immunized with an inactivated Aeromonas hydrophila and then introducing saturated ammonium sulfate solution to purify the IgY from crude extract, this study evaluated the immunocompetence recovery and antibacterial activity of IgY in vitro. The results showed that the immunocompetence recovery were 78.34% in the crude extraction suspension with 10 × distilled water dilution at pH 5.0 and 64.1% in purification suspension with 33%(v/v) saturated ammonium sulfate solution as precipitates. The purified IgY was of high purity as shown by SDS-PAGE. The crude extraction of IgY abolished the growth of A. hydrophila at a concentration of 1.0 mg/mL within 18 hours. In conclusion, the specific IgY from immunized hens could provide a novel alternative approach to prevention and control of diseases caused by A. hydrophila infection in several aquatic species.